Self‐Supported CuO In‐Situ‐Grown on Copper Foil as Binder‐Free Anode for Lithium‐Ion Batteries. Issue 12 (24th March 2022) - Liu, Yang; Liu, Han; Cai, Xuesong; Li, Xingqiu; Chen, Yuan; Ye, Nini; Liang, Chenglu
Abstract: Transition metal oxides as anode materials for lithium‐ion batteries (LIBs) possess the advantages of high specific capacity and abundance. However, most reported transition metal oxides based active anode materials were coated on the copper current collector with the addition of inactive polymer binder and conductive agents, resulting in low utilization of active substances. To solve this problem, nanostructured CuO with different morphologies (CuO bunches, CuO nanosheets, CuO nanotubes) were in‐situ grown on the copper current collectors via a simple wet chemical oxidation method. The as‐obtained CuO@Cu foils were used directly as anode for LIBs. CuO nanotubes exhibited excellent electrochemical performance and sustained a reversible discharge specific capacity of 798 mA h g −1 after 60 cycles at 100 mA g −1 . At current density of 1000 mA g −1, a high specific capacity of 758 mA h g −1 can be obtained after 200 cycles. The satisfying electrochemical performances of the CuO nanotubes anode indicated that a stable composite structure of CuO@Cu foils was achieved in the binder free electrode. This work demonstrated the feasibility of this binder free strategy in the development of electrode materials for high performance lithium‐ion batteries design. Abstract : The binder free CuO NTs@Cu foil electrodes maintain a high capacity of 758 mA h g −1 after 200 cycles at the current of 1000 mA g −1, showing higher cycling stability than the commercial CuO electrode prepared with binder and conductive agents. This work suggested the feasibility of this binder free and self‐supporting strategy in battery design.